Dynamic Mechanical Assessment of Muscle Hyperalgesia in Humans: The Dynamic Algometer - Sara Finocchietti; Thomas Graven-Nielsen; Lars Arendt-Nielsen (Pain Research and Management)
BACKGROUND: Musculoskeletal pain is often associated with a nonhomogeneous distribution of mechanical hyperalgesia. Consequently, new methods able to detect this distribution are needed.